2021
DOI: 10.3390/ijerph18105051
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Nurses’ Burnout during the First Wave of Coronavirus Disease-19 in a University Hospital in Italy

Abstract: Safety of healthcare workers in hospitals is a major concern during the COVID-19 pandemic. Being exposed for several working hours per day to infected patients, nurses dealing with COVID-19 face several issues that lead to physical/psychological breakdown. This study focused on burnout and its associated factors in nurses working in an Italian University Hospital during the first wave of COVID-19 pandemic. We designed a web-based cross-sectional study addressed to nurses working at the University Hospital in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
3
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 36 publications
4
33
3
13
Order By: Relevance
“…44,45 In the current study, the majority of HCPs of both countries had high levels of disengagement (75.4%) and emotional exhaustion (98.6%) which is higher than the ndings among the Italian nurses which showed high levels of exhaustion( 76%) and disengagement (52%). 31 Our results were close to results of healthcare workers in Singapore which revealed 79.7% disengagement and 75.3% exhaustion with mean OLBI scores 2.38 and 2.50 for disengagement and exhaustion respectively 4 close to the mean scores of the current study which were 2.56 and 2.73 for disengagement and exhaustion respectively . The mean score of burnout of all participants of the present study was 2.64 ± 0.36 consistent with frontline nurses working in COVID-19 wards in Iran hospitals where the mean score of burnout was 2.61±0.27.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…44,45 In the current study, the majority of HCPs of both countries had high levels of disengagement (75.4%) and emotional exhaustion (98.6%) which is higher than the ndings among the Italian nurses which showed high levels of exhaustion( 76%) and disengagement (52%). 31 Our results were close to results of healthcare workers in Singapore which revealed 79.7% disengagement and 75.3% exhaustion with mean OLBI scores 2.38 and 2.50 for disengagement and exhaustion respectively 4 close to the mean scores of the current study which were 2.56 and 2.73 for disengagement and exhaustion respectively . The mean score of burnout of all participants of the present study was 2.64 ± 0.36 consistent with frontline nurses working in COVID-19 wards in Iran hospitals where the mean score of burnout was 2.61±0.27.…”
Section: Discussionsupporting
confidence: 88%
“…Results of the current study revealed a high percentage of burnout in both countries, which was 77% among the Egyptian HCPs and 71% among the Sudanese HCPs. These results were less than COVID-19 related burnout which was 89.1% among nurses working in a university hospital in Italy, 31 which was conducted during the rst wave of the COVID-19 pandemic in contrast to the current study which was conducted during the third wave of the COVID-19 pandemic. Moreover, the prevalence of burnout in the current study is less than reported prevalence among Egyptian ICU workers which was 87.4% 32 .…”
Section: Discussioncontrasting
confidence: 85%
“…The most pronounced problems overall were the fear of infecting relatives, stress due to changes in tasks, physical or mental exhaustion and, as a protective factor, perceived protection by employers. Similar findings were reported by Belanti et al, 2020, who found that workload and lack of emotional support at the workplace were particularly predictive of mental distress in terms of burnout among nurses during the pandemic [ 38 ]. A study on French HCWs in intensive care identified the fear of infecting themselves or relatives with the virus as a predictor of various mental health problems [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…It is very important to note that this study being conducted during 1st wave of the pandemic in Egypt, explained the high degree of work-related stress that can be attributed to the novelty of the disease and the lack of international guidance for the use of medications. The high workload was also due to the large number of patients admitted since patients suffering from a mild degree of COVID-19 were also admitted being put under observation (Bellanti et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%